Optimisation of chemical constituents on enzyme-induced carbonate precipitation in test-tube and soil. Issue 3 (21st June 2021) - Ahenkorah, Isaac; Rahman, Md Mizanur; Karim, Md Rajibul; Beecham, Simon
Abstract : Enzyme-induced carbonate precipitation (EICP) is a bio-cementation technique and a sustainable method of ground improvement. This study examines the influence of the concentrations of substrates [ S 0 ] and enzymes [ E 0 ] as well as enzyme activity ( A E ) on the calcium carbonate (CaCO3 ) precipitation ratio (PR) using 130 test-tube experiments. It was found that the effect of enzyme concentration and activity on PR can be explained using a normalisation of [ E s ] = [ E 0 ] × A E, where [ E s ] is the adjusted enzyme concentration. PR increased non-linearly with increasing [ E s ]/[ S 0 ] and reached 100% at a threshold [ E s ]/[ S 0 ] value of approximately 20 kU/mol. An exponential function was developed that could capture the relationship between PR and [ E s ]/[ S 0 ] with reasonable accuracy. This observation was further evaluated with data from the literature consisting of a further 100 test-tube experiments. EICP solutions consisting of [ E s ]/[ S 0 ] = 20 kU/mol were found to be optimum for soil treatment. The established function was later extended to predict strength gain as measured by the unconfined compressive strength (UCS) and the splitting tensile strength (STS) for EICP-treated soils and could predict the strength gain (UCS/STS) with reasonable accuracy. Results from scanning electron microscopy images, energy-dispersive X-ray spectroscopy and X-ray powder diffraction showed that the precipitated calcium carbonate in test tubes and treated soil was mostly calcite crystals with different morphologies, possibly due to the level of purity of the urease enzyme used.